Peran Guru dalam Mengembangkan Keterampilan Sosial Anak Dimasa Pandemi Covid-19 Pada Kelompok B di TK Nusa Indah Toto Utara - Irvin Novita Arifin; Setiyo Utoyo; Evita Paputungan (Student Journal of Early Childhood Education, 2023)
The purpose of this study was to determine the teacher's role in developing children's social skills during the Covid-19 pandemic in group B at the North Nusa Indah Toto Kindergarten, Tilongkabila District, Bone Bolango Regency. This type of research uses a qualitative descriptive approach. From the results of the study it can be seen that the teacher's role in developing children's social skills during the Covid 19 pandemic in group B at Nusa Indah Toto North Kindergarten, Tilongkabila District, Bone Bolango Regency was carried out through five roles, namely the teacher's role as a guide, informator, class manager, facilitator, and communicator well done. The role of the teacher as a facilitator is carried out by the teacher providing facilities that allow for the convenience of children's learning activities, the role of the teacher as a communicator is carried out by the teacher being a friend, or a child's confidant when the child is having problems at home.